Morphology and stoichiometry control of hierarchical CuInSe2/SnO2 nanostructures by directed electrochemical assembly for solar energy harvesting - Sun, Juan (2013)
CuInSe2/SnO2 core–shell and hierarchical branched nanostructures were produced by directed electrochemical assembly. By changing the spatial electric field along the deposition region, we can control the morphology and stoichiometry of deposited product from In-poor-CuInSe2 nanoparticles to near stoichiometry CuInSe2 branched nanowires. A combination of FESEM, TEM, XRD and Raman spectroscopy investigations reveals that both morphology and chemical compositions of CuInSe2 strongly depend on the spatial electric field distribution on the SnO2/Si substrate. We observed that higher reducing potential can assist the formation of CuInSe2 with uniform coverage at the cathode side, but only In-poor-CuInSe2 nanoparticles are formed on the anode side. Optical and photo-electrochemical examination confirmed the potential application of these core–shell nanostructures for solar energy harvesting.